Methodology from the Bioethics Committee to Address Congenital Malformations - Nohora Montero García (Revista Colombiana de Bioética, 2015)
The University Hospital of Neiva, includes the most critical cases of Surcolombiana Region in the field of congenital malformations in perinatal medicine. These conditions involve a number of intractable conflicts, for medical personnel and the patient’s family. Experience has shown that ignorance of the basic theoretical bioethics guidelines and methodology for troubleshooting some people working in health, has resulted in the deterioration of the quality of life of families, the suffering of newborns by practices also lead to futile therapeutic cruelty and worse, to the realization of eugenic abortions resulting from medical suggestions that have left serious psychological consequences on the mother. In this attempt issues are addressed not only ethical, but delves into the existing dilemmas in such situations and are covered in turn, the discussion on therapeutic processes from the futility of medical treatment to the therapeutic obstinacy and the various aspects to be taken into account against the dilemma involved the limitation of treatment.